A Journal of One’s Own? Beginning the Project of Historicizing the Development of Women’s Law Journals - Batlan, Felice (Columbia Journal of Gender and Law, 2003)
Since the 1970s, feminism has helped transform the university and the production of knowledge. Not only have increasing numbers of female students, professors, and administrators entered universities, they have also created women’s studies programs and courses, which have been slowly integrated into the various disciplines and university curricula. Further, feminism has spurred scholars to question traditional ways of knowing and teaching, academic disciplines, categorizations of knowledge, scholarly methodologies, and the university’s separation from the broader community. One component in this production and distribution of new knowledge has been the establishment of feminist academic journals such as Feminist Studies (1972), Women’s Studies (1972), Signs: A Journal of Women in Culture and Society (1975), and Frontiers: A Journal of Women’s Studies (1975). These journals created a space for the development of a body of literature that was oppositional but also sanctioned, institutionalized, and eventually legitimated. Feminism has also entered legal academia and had far-reaching effects on it, though these have been slower to take shape and often have faced resistance. Within legal academia, somewhat later than the development of the major feminist academic journals, women’s law journals were founded-not by established scholars but rather by law students. Leaving aside the peculiar origins and development of law reviews and law journals as a whole, there are unique features of the story of women’s law journals-of their origin, evolution, and problematic status–that deserve study.